OP0203-HPR Does Enat-Focused Education Improve Health Outcomes in Ra? A Randomised Controlled Trial. (10th June 2014) - Hardware, B.; Young, T.; Johnson, D.B.; Ndosi, M.; Hale, C.; Maxwell, J.R.; Roussou, E.; Adebajo, A.
Abstract : Objectives: The aim of this study was to evaluate the effectiveness of ENAT-focused patient education on self-efficacy, health status and patient knowledge. We hypothesised that, the use of the ENAT to help focus patient education on patients' priority educational needs, would improve their self-efficacy and health status. Methods: This study was a pragmatic 7-centre RCT. The inclusion criteria were: a diagnosis of RA, age 18+ years and ability to complete questionnaires. Patients were randomised to either the ENAT group where patients completed the ENAT which was then used as a template by the Clinical Nurse Specialist (CNS) to meet their educational needs; or usual care by CNS without the ENAT. Patients were seen at baseline then at weeks 16 and 32. The outcomes were self-efficacy (ASES), health status (AIMS2-SF) and patient knowledge (PKQ). We investigated between-group differences (t-test) and trends over time (repeated measures ANOVA). Intention-to-treat results are reported (multiple imputation for missing data) except AIMS2-SF-Work data, where complete case analysis was used for patients who were working. Results: A total of 132 patients were recruited, 70 EG (53%) and 62 UC (47%). Their mean (SD) age was 54 (12.3), 56 (13.3) and disease duration 5.2 (4.9), 6.7 (8.9) for EG and UC respectively. Questionnaire completion rates (EG, UC) were; 97%, 97% (baseline) 90%, 85% (week 16) and 79%, 76% (week 32). Significant between-group differences were found, in favour of the EG at week 32 in ASES-Pain, MD (SE)=-4.36 (1.6), t=-2.72, P=0.008; ASES-Other symptoms, MD (SE)=-5.84 (3.06), t=-3.07, p=0.003; AIMS2-SF Symptoms, MD (SE)=1.04 (0.41), t=5.54, p=0.013 and AIMS2-SF Affect, MD (SE)=0.86 (0.30), t=2.84, p=0.006. Between-group differences were not significant in other time-points or in the total PKQ score. Table 1 presents within-group changes over time. Scores are mean (SD) after multiple imputations. The ENAT group showed significant improvements in most outcomes while usual care showed significant improvements only on AIMS2-SF work. Conclusions: This is the first study to report the effects of ENAT-focused education in people with RA, suggesting improvements in self-efficacy and aspects of health status. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3541